"Eat your Fruits and Vegetables and Don't Get Malaria": Linkages between Agriculture, Nutrition, and Health in Uganda. - Griffiths, Jeffrey. (Tufts University. Tisch Library., 2017)
This presentation discusses links between agriculture and nutritional health in Uganda.; Keywords: Topics covered include malaria, anemia, and plant based foods vs.; Keywords: animal sourced foods.; Keywords: Uganda, malaria, anemia, fruit and veg, livestock, nutrition, agriculture, Tufts University.; NIL Presentations 2013-2015.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy